Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Böer, Nils Tobias; Kunde, Wilfried (Human Movement Science)
Typically, head fakes in basketball are generated to, and actually do, deteriorate performance on the side of the observer. However, potential costs at the side of the producer of a fake action have only rarely been investigated before. It is thus not clear yet if the benefit (i.e., slowed reactions in the observer) of performing a head fake is overestimated due to concurrently arising fake production costs (i.e., slowed performance in the producer of a head fake). Therefore, we studied potential head-fake production costs with two experiments. Novice participants were asked to generate passes to the left or right side, either with or without head fakes. In Experiment 1, these actions were determined by an auditory stimulus (i.e., a 440 Hz or 1200 Hz sinus or jigsaw wave). After an interstimulus interval (ISI) of either 0 ms, 800 ms, or 1500 ms, which served the preparation of the action, the cued action had to be executed. In Experiment 2, passing to the left or right, either with or without a head fake, was determined by a visual stimulus (i.e., a player with a red or blue jersey defending either the right or left side). After an ISI of either 0 ms, 400 ms, 800 ms, or 1200 ms, the cued action had to be executed. In both experiments, we observed higher reaction times (RTs) for passes with head fakes as compared to passes without head fakes for no and an intermediate preparation interval (from ISI 0 ms to 800 ms), but no difference for a long preparation interval (for an ISI of 1200 ms and 1500 ms). Both experiments show that generating fake actions produces performance costs, however, these costs can be overcome by a longer preparation phase before movement execution.
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Paschen, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Agreement and consistency of five different clinical gait analysis systems in the assessment of spatiotemporal gait parameters - Rudisch, Julian; Jöllenbeck, Thomas; Vogt, Lutz; Cordes, Thomas; Klotzbier, Thomas Jürgen; Vogel, Oliver; Wollesen, Bettina (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The role of different directions of attention on the extent of implicit perception in soccer penalty kicking - Memmert, Daniel; Noël, Benjamin; Machlitt, Daniel; van der Kamp, John; Weigelt, Matthias (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Dissociative effects of normative feedback on motor automaticity and motor accuracy in learning an arm movement sequence - Zobe, Christina; Krause, Daniel; Blischke, Klaus (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Balance exergames increase cortical activity in frontal areas of the brain - Anders, Phillipp; Lehmann, Tim; Müller, Helen; Molde, Ingunn; Blix Grønvik, Karoline; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

P108: Balance exergames improve movement characteristics of body weight transfer - Anders, Phillipp; Blix Grønvik, Karoline; Molde, Ingunn; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

P107 Balance exergames increase cortical activity in frontal areas of the brain - Anders, Phillipp; Lehmann, Tim; Müller, Helen Martha; Molde, Ingunn; Blix Grønvik, Karoline; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

P107 Balance exergames increase cortical activity in frontal areas of the brain - Anders, Phillipp; Lehmann, Tim; Müller, Helen Martha; Molde, Ingunn; Blix Grønvik, Karoline; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Error Feedback Frequency Affects Automaticity But Not Accuracy and Consistency After Extensive Motor Skill Practice - Krause, Daniel; Agethen, Manfred; Zobe, Christina (Journal of Motor Behavior)
Keywords: Cognitive Neuroscience; Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; Biophysics

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Effects of bandwidth feedback on the automatization of an arm movement sequence - Agethen, Manfred; Krause, Daniel (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Effects of model orientation on the visuomotor imitation of arm movements: The role of mental rotation - Krause, Daniel; Kobow, Sven (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Shrinking of anionic polyacrylate coils induced by Ca2+, Sr2+ and Ba2+: A combined light scattering and ASAXS study - Schweins, R.; Goerigk, G.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Confined phonons in glasses - A study by nuclear inelastic absorption and Raman scattering - Asthalter, T.; Bauer, Matthias; van Bürck, U.; Sergueev, I.; Franz, H.; Chumakov, A.I. (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Collapse of sodium polyacrylate chains in calcium salt solutions - Schweins, R.; Huber, Klaus (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology